Increasing Sales of Pandan Mat Artisans in Kadumaneuh Village Through Business Assistance Based on Internship Activities - Huda, Nurul; Gani, Ariel Nian; Rofi'i, Muhammad; Haryanti, Sri Chusri; Tulusmiyanti, Novia; Dimitra, Dwina Reflie (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This project aims to increase the sales of pandan mat artisans in Kadumaneuh Village by addressing marketing challenges and introducing innovative business concepts.Method: The approach included outreach, mentoring, and creating a promotional website. Artisans were trained in business concepts and product innovation, followed by mentoring to apply these ideas, and a website was developed for broader market reach.Practical Applications: The website serves as a promotional tool to expand sales, while the training equips artisans with better business knowledge, helping them adapt and compete more effectively.Conclusion: The project improved artisans' understanding of business concepts, though no significant change was noted in comparative analysis. The mentoring and website development are expected to bring long-term benefits to the artisans' businesses.